Phytosynthesis of intracellular and extracellular gold nanoparticles by living peanut plant (Arachis hypogaea L.) - Raju, Dugyala; Mehta, Urmil J.; Ahmad, Absar (Biotechnology and Applied Biochemistry, 2012)
Inorganic nanomaterials of different chemical compositions are conventionally synthesized under harsh environments such as extremes of temperature, pressure, and pH. Moreover, these methods are eco-unfriendly and cumbersome, yield bigger particles, and agglomerate because of not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions, namely room temperature, atmospheric pressure, and physiological pH. These methods are reliable, eco-friendly, and cheap. In this paper, we report for the first time the extracellular and intracellular synthesis of gold nanoparticles (GNPs) using living peanut seedlings. The formed GNPs were highly stable in solution and inside the plant tissue. Transmission electron microscopy revealed that extracellular GNPs distributions were in the form of monodispersed nanoparticles. The nanoparticles ranged from 4 to 6 nm in size. The intercellular nanoparticles were of oval shape and size ranged from 5 to 50 nm. Both extracellular and intracellular nanoparticles were further characterized by standard techniques. The formed GNPs inside the plant tissue were estimated by inductively coupled plasma spectrometry. This opens up an exciting possibility of a plant-based nanoparticle synthesis strategy, wherein the nanoparticles may be entrapped in the biomass in the form of a film or produced in the solution, both of which have interesting applications.
Keywords: cells; extracellular; living plant; Peanut; root; TEM